Analysis of High School Learners on Zakat and Waqf Management Program at Islamic Higher Education: A Mixed Methods Approach - Nopiardo, Widi; Asrida, Asrida; Mariyani, Fitri (Islamic Studies and Development Center in collaboration with Department of Islamic Education Universitas Negeri Padang, 2024)
The Zakat and Waqf Management Study Program always tries to socialize this Study Program to high school students or equivalent, so that the Study Program is in demand by students who want to continue to the university level. If this Study Program is not recognized by high school students, then the tendency is to get challenges in students' interest in it. This study aims to explain the perceptions of high school students towards the Zakat and Waqf Management Study Program at Islamic Religious Universities. This type of research is mixed methods with an explanatory mixed method design approach. Data collection techniques through questionnaires, interviews and documentation. The number of informants for questionnaires and interviews was 99 people. Data analysis techniques through data reduction, data presentation, and conclusion drawing. Quantitative data analysis techniques use SPSS while qualitative data analysis techniques use thematic methods. Data validity assurance techniques through source triangulation. Both data analysis results show that the perceptions of most informants are positive and good towards this Study Program. Regarding the percentage index of the perception variable items, the average percentage index is 79.92. Thus it can be interpreted that the percentage score interval means good, because it is in the interval 60-79.99%. Based on in-depth interviews conducted, information was obtained that in general, high school students in Tanah Datar Regency had a good perception of the Zakat and Waqf Management Study Program at Universitas Islam Negeri Mahmud Yunus Batusangkar. The benefit of this research is to help the development of the Zakat and Waqf Management Study Program in socializing it to high school students.